2018
DOI: 10.1186/s12885-018-4458-7
|View full text |Cite
|
Sign up to set email alerts
|

Golgi phosphoprotein 3 (GOLPH3) promotes hepatocellular carcinoma progression by activating mTOR signaling pathway

Abstract: BackgroundHepatocellular carcinoma (HCC) is the sixth most common cancer and the second leading cause of cancer-related deaths worldwide. Despite new technologies in diagnosis and treatment, the incidence and mortality of HCC continue rising. And its pathogenesis is still unclear. As a highly conserved protein of the Golgi apparatus, Golgi phosphoprotein 3 (GOLPH3) has been shown to be involved in tumorigenesis of HCC. This study aimed to explore the exact oncogenic mechanism of GOLPH3 and provide a novel diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…Very strikingly, altered expression of GOLPH3 and Myosin-18A are associated with a range of malignant phenotypes including tumour secretion (41), increased trafficking to the leading edge of migratory cells and consequently augmented cell motility, loss of cell-cell adhesion and invasion (39,45,49,50,(218)(219)(220)(221)(222)(223)(224)(225). However, while this model is strongly supported by a wealth of experimental data, there is at least one report indicating that Myosin-18A is neither localised to the Golgi nor required for its characteristic ribbon like structure (226).…”
Section: Golph3 -A Golgi Pi4p Effector and Oncoproteinmentioning
confidence: 99%
“…Very strikingly, altered expression of GOLPH3 and Myosin-18A are associated with a range of malignant phenotypes including tumour secretion (41), increased trafficking to the leading edge of migratory cells and consequently augmented cell motility, loss of cell-cell adhesion and invasion (39,45,49,50,(218)(219)(220)(221)(222)(223)(224)(225). However, while this model is strongly supported by a wealth of experimental data, there is at least one report indicating that Myosin-18A is neither localised to the Golgi nor required for its characteristic ribbon like structure (226).…”
Section: Golph3 -A Golgi Pi4p Effector and Oncoproteinmentioning
confidence: 99%
“…An increasing number of papers has shown that GOLPH3 drives cancer in several other solid tumors such as Neuroblastoma (NB) [42], Non-Small Cell Lung Cancer (NSLC) [89], epithelial ovarian carcinoma [90], prostate cancer [91,92], gastric cancer [93], and hepatocellular carcinoma [94,95] ( Figure 2). Recent reports indicate that GOLPH3 overexpression can be used as a positive biomarker for tumor progression and poor survival in these cancer types [89][90][91][92][93][94][95][96][97][98]. Experimental data in cancer cell lines or in nude mice revealed the role of GOLPH3 in cell proliferation, metastasis formation and angiogenesis ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…For HCC diagnosis, the accuracy of Golgi protein 73 was higher than alphafetoprotein, which is used for clinical diagnosis [26][27]. Liu et al (2018) suggested that GOLGPH3…”
Section: Discussionmentioning
confidence: 99%
“…acts an oncogene in HCC development and progression by activating the mTOR pathway, which is also a potential target for HCC diagnosis and therapy [28]. Lee et al (2018) indicated that the Golgi transmembrane protein TEME165 contributes to the progression of HCC [29].…”
Section: Discussionmentioning
confidence: 99%